STUDI PROSES PEMBUATAN DAN PEMASANGAN LADDER PADA PEMBANGUNAN KAPAL LA LUMIERE 9 - Arianto, Pratama Yuli; Fasya, Nurisa Sharani; Yasim, Ahmad; Puspita, Hery Indria Dwi (Jurnal Inovasi Teknologi Manufaktur, Energi dan Otomotif, 2025)
Ship ladders are an important element in mobility between rooms or decks on a ship. On the La Lumiere 9, which is a luxury yacht made from FRP, the ship's ladder requires material that is strong, light, and has high durability to sea conditions that have high salt levels. This research explains the procedures for using FRP composite materials in the process of making and installing ship ladders, guided by the International Convention for Safety of Life At Sea (SOLAS). The results of this research will provide practical guidance for maritime companies and the ship industry who are interested in utilising the potential of composite materials in the development of more sophisticated and durable ship ladders. It is hoped that ship ladders made from FRP can face the challenges of the maritime environment more reliably.